Patriarchal Bias in the Interpretation of Verses on Interfaith Marriage: A Historical-Linguistic Study by Aksin Wijaya - Haitomi, Faisal; Aji, Essyarovis Lutfiantoro; Barokah, Laelatul (Institut Agama Islam Negeri (IAIN) Keiri, 2023)
This article is presented with the aim of re-describing Aksin Wijaya's interpretation of the interfaith marriage verse. This research is driven by the assumption of a strong patriarchal cultural influence in the interpretation process. This is further supported by the existence of a fatwa stating that a Muslim man is allowed to marry a woman from the People of the Book, but the reverse does not apply to women. Additionally, the narrowing and expanding of meanings when interpreting the above verse are also strong reasons for prioritizing this research. The author utilizes historical linguistic analysis as the research method. In simple terms, historical analysis is used to establish the Quranic verse as a social fact, while linguistics will examine the sentence structure and diction used in the Quran. This research concludes that interfaith marriage, according to Aksin Wijaya, is a historically rooted problem, and therefore, the established rules are also dynamic, depending on the social conditions in which the verse is interpreted.